Análisis de riesgo ante fenómenos de remoción en masa, en el barrio Sagrado Corazón de Jesús de la ciudad de Chimbo - Abril Mueses, Oscar David (2020)
The present work is carried out with the determination to identify are the detonating and conditioning factors of the Sacred Heart of Jesus neighborhood of the Chimbo canton and, as these in turn are related in the occurrence of mass movements. Through the methodology proposed by Mora Vahrson, through indicators it is weighted according to the characteristics in situ at levels of susceptibility ranging from Low, Medium and High. By incorporating the Geographic Information Systems, a spatial visualization of the areas most susceptible to mass movements of the canton was obtained, through which structural and non-structural risk management measures were established, with an ecosystem-based approach. It was identified that 28.67% of the houses present in the rainy season mass movement problems, however despite being recurrent the problems of the local authorities have not taken the relative measures to reduce the limitations of the houses, therefore It is intended that the results of the investigation be incorporated into the land use plan and the population that really needs to be served.